Who is steering the jurisprudence of the European Court of Justice? The influence of Member State submissions on copyright law. Issue 4 (18th May 2020) - Favale, Marcella; Kretschmer, Martin; Torremans, Paul L. C.
Abstract: The juridification of the European policy process is increasingly fragile, and little understood. This study develops a novel methodology to investigate the influence of Member States on the rulings of the Court of Justice of the European Union (CJEU). The focus is on the domain of copyright law which has seen a dramatic escalation of preliminary references to the Court, indicating a normative void. Examining 170 documents relating to 42 cases registered between 1998 and 2015, we measure empirically the impact of submissions by Member States and the European Commission on the interpretation of copyright concepts. We show that France is the most influential country by some distance, both in terms of the number of interventions (an 'investment' in policy) and in terms of persuasive power (arguments adopted by the Court). The evidence also suggests that the departure of the UK from EU litigation will disturb the delicate balance of CJEU jurisprudence.